Visualization of a functionally enhanced GFP-tagged galanin R2 receptor in PC12 cells: Constitutive and ligand-induced internalization - Xia, Sheng (National Academy of Sciences, 2004)
Trafficking of the galanin R2 receptor (GALR2) fused with enhanced GFP (EGFP) was studied by using confocal fluorescence microscopy. The fusion protein was predominantly localized on the plasma membrane with some intracellular fluorescent structures (vesicles), mainly in the perinuclear region. Incubation with galanin resulted in a concentration-dependent increase in intracellular Ca(2+) concentration levels, suggesting that the GALR2-EGFP conjugate is functional. After blocking endocytosis with methyl-β-cyclodextrin GALR2-EGFP expression was increased on the surface and decreased in the cytoplasm. Blocking endocytic recycling with monensin caused an increase of intracellular GALR2-EGFP accumulation and a decrease of fluorescence on the plasma membrane. GALR2-EGFP on the plasma membrane was internalized within 5-10 min after treatment with galanin or AR-M1896, a selective GALR2 agonist, with a dramatic reduction in plasma membrane localization and appearance in intracellular vesicles. Neither M35 nor M40, two galanin analogues with putative antagonistic action, prevented GALR2 agonist-induced internalization of GALR2-EGFP, suggesting that they are not antagonists at this receptor under the present circumstances. Galanin stimulation at low temperature caused GALR2-EGFP aggregation and clustering on the surface but no translocation to cytoplasm. After coincubation with galanin the GALR2-EGFP was colocalized with internalized Texas red-transferrin, a marker of the clathrin endocytic pathway. Hyperosmotic sucrose inhibited internalization of GALR2-EGFP. Taken together these findings indicate that GALR2 undergoes constitutive endocytosis and recycling and that both ligand-independent and ligand-dependent internalization use the clathrin-dependent endocytic recycling pathway.